2014
DOI: 10.3892/mmr.2014.2195
|View full text |Cite|
|
Sign up to set email alerts
|

microRNA-145 inhibits osteosarcoma cell proliferation and invasion by targeting ROCK1

Abstract: Abstract. Osteosarcoma (OS), a malignant mesenchymal sarcoma, is the most frequent primary bone tumor, with a peak incidence in young children and adolescents. The downregulation of microRNA-145 (miRNA/miR-145) has previously been identified to be associated with the aggressiveness and metastasis of OS. However, the detailed regulatory mechanism by which miR-145 inhibits OS remains largely unknown. The present study demonstrated that miR-145 was significantly downregulated in OS tissues and KHOS and U2OS cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…These findings suggested that the inhibitory effect (12) reported that miR-340 suppressed osteosarcoma tumor growth and metastasis by directly targeting ROCK1 and Wang et al (22) revealed that miR-335 inhibited migration and invasion by targeting ROCK1 in osteosarcoma cells (22). In addition, miR-145 was demonstrated to inhibit osteosarcoma cell proliferation and invasion by targeting ROCK1 (23). The present study demonstrated that high expression of ROCK1 was inversely correlated with miR-144 expression, highlighting the role of miR-144 in the regulation of cell proliferation, migration and invasion by targeting ROCK1 in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 90%
“…These findings suggested that the inhibitory effect (12) reported that miR-340 suppressed osteosarcoma tumor growth and metastasis by directly targeting ROCK1 and Wang et al (22) revealed that miR-335 inhibited migration and invasion by targeting ROCK1 in osteosarcoma cells (22). In addition, miR-145 was demonstrated to inhibit osteosarcoma cell proliferation and invasion by targeting ROCK1 (23). The present study demonstrated that high expression of ROCK1 was inversely correlated with miR-144 expression, highlighting the role of miR-144 in the regulation of cell proliferation, migration and invasion by targeting ROCK1 in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 90%
“…Osteosarcoma is a highly malignant primary bone tumor, with bone-like tissue formed by tumor cells (1). As one of the early symptoms of osteosarcoma, patients experience intermittent pain, even prior to tumor formation.…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma is a highly malignant primary tumor occurring in the bone and associated tissues, characterized by a bone-like tissue consisting of tumor cells (1). As the disease progresses, osteosarcoma can progressively harm the health of the patients by causing lump formation, organ dysfunction and fractures (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Often occurring in the bones and skeleton or their auxiliary tissues, osteosarcoma displays characteristics of osteoid tissues directly formed by tumor cells (1). The majority of patients with osteosarcoma undergo amputation to remove the affected bone; however, post-amputation five-year survival rates remain low at 5%-20% (2).…”
Section: Introductionmentioning
confidence: 99%